(untitled) (Scientific journal of the Fergana State University, 2025)
In this paper, Nitroso-R-salt was used as a new highly efficient and selective also cost-effective analytical reagent the determination for Fe (III) ion. Nitroso-R-salt was immobilized on the sorbent and the analytical signal was measured by ultra-violent spectroscopy. The disodium salt (nitroso-R-salt) of 1-nitroso-2-naphthol-3,6-disulfoacid immobilized on polyacrylonitrile (PPF) fiber modified with polyethylene where polyamine used as a carrier. Mechanisms of complex formation and optimal conditions were studied. According to results showed that the complex of iron (III) ion with immobilized nitroso-R-salt is formed when the molar ratio is 1:1. The results were confirmed by absorption, ultra-violent spectroscopy and IR analysis.